Leiomyomata of the genitourinary tract: A case series from the "rare urological neoplasm" registry. (April 2013) - Oderda, Marco; Mondaini, Nicola; Bartoletti, Riccardo; Vigna, Dario; Fiorito, Chiara; Marson, Francesco; Peraldo, Francesca; Bosio, Andrea; Maletta, Francesca; Pacchioni, Donatella; Gontero, Paolo
Abstract Objective. Leiomyomata are benign neoplasms that are rarely encountered in the genitourinary tract outside the uterus. Pathological confirmation is always needed for definitive diagnosis, in order to rule out malignancies such as leiomyosarcoma. In cases of small leiomyomata, a surveillance strategy can be suggested, although the preferred approach is complete resection. Prognosis seems to be excellent, but available data are based on few, inconsistent series, as is often the case with rare neoplasms. This article presents long-term follow-up data from the most heterogeneous series, in terms of anatomical location, currently available. Material and methods. The present series of 33 genitourinary leiomyomata was retrieved after joining the "rare urogenital neoplasm" registry of two Italian regions. Two pathologists jointly reviewed all pathological slides and confirmed the diagnosis of leiomyoma. Results. Sixteen cases were localized to the scrotum, eight to the bladder, five to the kidney, two to the prostate, one to the urethra and one to the penis. Mean patient age was 58.4 (range 32–80) years. Mean follow-up was 15.5 (range 2–20) years. Conclusions. In this highly heterogeneous series, the disease showed excellent long-term recurrence- and progression-free interval. The accuracy of pathological diagnosis, along with the indolent long-term course, make the role of active surveillance amenable for asymptomatic cases, particularly where surgery may result in overtreatment.